2015
DOI: 10.15837/ijccc.2015.4.1514
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Design and Deployment of Aqua Monitoring Systems Using WSNs and Correlation Analysis

Abstract: The roots of innovation are extending towards every field to provide ace solution. We cater an ace solution for aquaculture, where their yields (shrimp, fish, etc.) depends on the ponds water characteristics. The parameters depending on water must kept at certain optimal levels for better cultivation of Aqua. The parameters of water extremely project alterations during the day and also alter depending upon the environmental conditions i.e., it is necessary to monitor these parameters with high frequency. We ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…If in Figure 5 the error continues to increase after the end of the simulation time, then in Figure 6 the error reaches a smaller value and after that does not increaseะธ [38]. Let us show that the obtained values differ from the values that could be obtained from relations (3). Indeed, for this model ๐‘˜ ๐‘š = 4.05678,๐‘‡ ๐‘š = 7.10778, ๐œ ๐‘š = 1.43256, while calculations using relation (3) would give the following values: ๐‘˜ ๐‘š = 4, ๐‘‡ ๐‘š = 1,๐œ ๐‘š = 6.75.…”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…If in Figure 5 the error continues to increase after the end of the simulation time, then in Figure 6 the error reaches a smaller value and after that does not increaseะธ [38]. Let us show that the obtained values differ from the values that could be obtained from relations (3). Indeed, for this model ๐‘˜ ๐‘š = 4.05678,๐‘‡ ๐‘š = 7.10778, ๐œ ๐‘š = 1.43256, while calculations using relation (3) would give the following values: ๐‘˜ ๐‘š = 4, ๐‘‡ ๐‘š = 1,๐œ ๐‘š = 6.75.…”
Section: Methodsmentioning
confidence: 79%
“…The ganetxl optimization model for automation of water systems is used, improvement of the correct water distribution is considered and it is shown that epanet2 can be adapted for successful modeling of intermittent water systems, and a set of solutions for economic or social factors is proposed [2]. According to the water distribution and reception system, analytical work was carried out on two different models, in which data was transmitted via global system for mobile communications (GSM) to a database at the receiving station, interfaces and observers were used, and was analyzed on the basis of innovative solutions [3]. Trial work was carried out on two river water resources, water purification was carried out using modern methods to reduce the turbidity phenomenon in several sectors of the river, special sensors for water composition and ph were applied, a comparative analysis of parameters for special samples was carried out [4].…”
Section: Introductionmentioning
confidence: 99%
“…For densely deployed sensor networks, there is a certain similarity between the data collected by the geographically adjacent nodes [34]. Therefore, the data correlation of the neighbor nodes can be implemented to measure the sensor's credibility.…”
Section: B Nodes's Credibilitymentioning
confidence: 99%
“…In work [14-17], the cluster head is equipped with a GPRS (general packet radio service) module that can provide a longer range. In work [18,19], the sensor node directly uses the GSM/GPRS modem for long-range communication. However, the GPRS module has higher power consumption and operating costs, and the network coverage and capability depend on the existing infrastructure.LPWAN represents a new trend in the evolution of IoT technologies.…”
mentioning
confidence: 99%